Gambaran Student Engagement dalam Pembelajaran di Era New Normal - Nolla Gladisia; Nadhirotul Laily; Noer Suci Endah Puspitaningrum (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
This study is to find out the description of Student Engagement in learning in the New Normal Era in grade VII students of SMP